Recent advances in lanthanide-doped up-conversion probes for theranostics - Xu, Danyang; Li, Chenxu; Li, Wenjing; Lin, Bi; Lv, Ruichan (Frontiers in Chemistry, 2023)
Up-conversion luminescence, or anti-stokes luminescence, refers to the phenomenon that materials emit short-wavelength and high-frequency light when excited by long-wavelength and low-frequency light. Lanthanides-doped upconversion nanoparticles (Ln-UCNP) are widely used in biomedicine due to their excellent physical and chemical properties such as high penetration depth, low light damage and light conversion ability. Here, the latest developments in the synthesis and application of Ln-UCNP are reviewed. First, the advanced methods used to synthesize Ln-UCNP in recent years are introduced, and then four strategies for enhancing upconversion luminescence are analyzed, followed by an overview of the applications of which in phototherapy, bioimaging and biosensing. Finally, the challenges and future prospects of Ln-UCNP are summarized.